## Submitted Questions

• #### Find the number of Marbles

In A, B, C are having some marbles with each of them. A has given B and C the same number of marbles each of them already have. Then, B gave C and A the same number of marbles they already have. Then C gave A and B the same number of marbles they already have. At the end A, B and C have equal number of marbles. (i) If x,y,z are the marbles initially with A,B,C respectively. Then find the...

#### Md Parvez Profile Answers by Md Parvez Questions by Md Parvez

• Mar 16th, 2011

First a,b and c have same number of marbles.a->xb->yc->znow a gave b and c so a->-xb->y+yc->z+znow b gave a and ca->-x+xb->0c->z+z+znow c gave a and ba->-x+x+xb->0+yc->zit means a have x, b have y and s have z.same as they had initially.

#### rakesh0814069 Profile Answers by rakesh0814069 Questions by rakesh0814069

• Aug 9th, 2010

step 1 a tob=yc=zend a=x-(y+z)      b=2y c=2zstep 2 B toc=2za=x-(y+z)enda=2(x-y-z)b=2y-(2z+x-y-z)=3y-z-xc=4zstep 3  C toa=2(x-y-z)b=3y-z-xnow b has=2(3y-z-x)